Circulating Soluble CD163: A Potential Predictor for the Functional Outcome of Acute Ischemic Stroke - Sun, Houchao; Zhang, Xiaogang; Ma, Jingxi; Liu, Zhao; Qi, Yunwen; Fang, Li; Zheng, Yongling; Cai, Zhiyou (Frontiers in Neurology, 2021)
Background: CD163 is a transmembrane glycoprotein receptor expressed on innate immune cells that sheds from the cell membrane and circulates as a soluble form (sCD163). This study aimed to investigate the circulating levels and clinical relevance of soluble CD163 (sCD163) in acute ischemic stroke (AIS). Methods: This study recruited 300 patients with AIS and 78 healthy controls. The patients were followed up for 1 month to observe the functional outcomes. The neurological functions of the patients were assessed using the NIH Stroke Scale (NIHSS) and the modified Rankin Scale (mRS). The plasma concentrations of sCD163 at the baseline (patient admission) were determined by ELISA. Results: We found that patients with AIS had significantly higher plasma sCD163 concentrations than the healthy control. Patients with high sCD163 concentrations had better functional outcomes than patients with low sCD163 concentrations. The plasma sCD163 concentrations were positively associated with the NIHSS scores and infarction volume at the baseline. The plasma sCD163 was positively associated with the improvement of the NIHSS scores but was negatively associated with the risk of poor functional outcomes during follow-up. Conclusions: These findings indicate that circulating sCD163 is a potential biomarker that is associated with disease severity and the functional outcome of AIS.